Anatomical and biochemical analyses reveal the mechanism of double-color formation in Paeonia suffruticosa ‘Shima Nishiki’ - Zhang, Xinpeng (3 Biotech, 2018)
Paeonia suffruticosa ‘Shima Nishiki’ is a very precious double-color cultivar because of its distinctive and colorful flowers. However, our understanding of the underlying mechanisms of its double-color formation is limited. The present study investigated the soluble sugar content, cell sap pH value and anatomical structure, anthocyanin composition and content and expression patterns of genes related to anthocyanin biosynthesis in the red and pink petals of the ‘Shima Nishiki’ cultivar. Here, we found that soluble sugar content, cell sap pH and the shape of outer epidermal cells were not the key factors that determine double-color formation. Five different anthocyanins were detected in both the red and pink petals, and the pelargonidin-3,5-di-O-glucoside (Pg3G5G) and pelargonidin-3-O-glucoside (Pg3G) contents in the red petals were significantly higher than those in the pink petals at every developmental stage. In addition, these gene expression patterns suggested that the significant differential expression of the dihydroflavonol 4-reductase gene (PsDFR) gene might play a key role in double-color formation. These results will provide a valuable resource for further studies unraveling the underlying genetic mechanisms of double-color formation in P. suffruticosa ‘Shima Nishiki’.